Pengaruh Kualitas Pelayanan PDAM, Tarif PDAM dan Tempat Pembayaran PDAM terhadap Penerimaan Pembayaraan PDAM - Indah Lestari; Dumadi Dumadi; Yenny Ernitawati (Jurnal Visi Manajemen, 2025)
This study aims to find out and test the influence of PDAM service quality, PDAM tariff and PDAM payment place on PDAM payment receipts. This research was conducted with a quantitative approach. The type of data in the form is primary data with questionnaires. The study population is PDAM customers in Brebes Regency. The determination of the number of samples in this study with the Slovin formula obtained 98 responses. The respondents' answer data was tested with validity and reliability tests. It is then tested with a classical assumption test. The data analysis technique was carried out by multiple regression test The results of the study showed that the quality of PDAM services partially affected the receipt of PDAM payments obtained a sig value = 0.000 < 0.05. Partially, the PDAM tariff affects the receipt of PDAM payments, obtaining a sig value = 0.000 < 0.05. Partially, the place where PDAM payments affect the receipt of PDAM payments obtained a sig value = 0.001 < 0.05. Simultaneously, the quality of PDAM services, PDAM tariffs and PDAM payment places affect PDAM payment receipts.